2021
DOI: 10.52794/hujpharm.962540
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory drugs ibuprofen, celecoxib, and etanercept prevented cyclosporine A form initiating depression-like behavior in mice

Abstract: Cyclosporine A (CYA), is used to prevent graft rejection, but it may cause depression in individuals. Anti-inflammatory drugs are associated with antidepressant effects, the aim was evaluating the effect of nonsteroidal anti-inflammatory drugs (NSAID) (ibuprofen, celecoxib), and tumor necrosis factor-α blocker (etanercept) pretreatment on depressive behavior induced by CYA (20 mg/kg) in male mice (25±2 g). The pretreatment with ibuprofen (50 mg/kg), or celecoxib (25 mg/kg) were applied intraperitoneal for 3 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In all preclinical studies (17/17, 100%), regardless of the depression model, antidepressant effect of celecoxib was reported. Most included reports have pointed to the antidepressant effect of celecoxib in monotherapy [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Interestingly, two studies indicated that celecoxib might enhance the antidepressant effects of fluoxetine and bupropion [75,88].…”
Section: Preclinical Studies-effect Of Celecoxib On Depression and Ma...mentioning
confidence: 99%
See 3 more Smart Citations
“…In all preclinical studies (17/17, 100%), regardless of the depression model, antidepressant effect of celecoxib was reported. Most included reports have pointed to the antidepressant effect of celecoxib in monotherapy [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. Interestingly, two studies indicated that celecoxib might enhance the antidepressant effects of fluoxetine and bupropion [75,88].…”
Section: Preclinical Studies-effect Of Celecoxib On Depression and Ma...mentioning
confidence: 99%
“…Interestingly, two studies indicated that celecoxib might enhance the antidepressant effects of fluoxetine and bupropion [75,88]. In nine studies, celecoxib alone or with co-administration of antidepressants improved behavioral despair in forced swimming test (FST) [74][75][76][80][81][82][84][85][86] and in four studies in tail suspension test (TST) [75,76,78,83]. In eight studies, a positive effect on anhedonia as measured by the sucrose preference test (SPT) was found [73,76,77,81,82,[84][85][86].…”
Section: Preclinical Studies-effect Of Celecoxib On Depression and Ma...mentioning
confidence: 99%
See 2 more Smart Citations